OPTIMASI SUHU ANNEALING UNTUK PRIMER g-SSR DAN EST-SSR PADA KACANG HIJAU (Vigna radiata L.) - Herman Herman; Lambok Nia Natalya; Suha Maudina Berampu; Dewi Indriyani Roslim (UIR Press, 2017)
Mungbean (Vigna radiata L.) is one of important legume in Indonesia. G-SSR and EST-SSR markers had been widely used in mungbean genetic diversity research. DNA isolation and DNA amplification are required to obtain genetic information about mungbean to obtain accurate data on the genetic diversity of mungbean. This study aims to determine the Temperature of annealing (Ta) of the g-SSR and EST-SSR primer pairs. The total DNA was isolated from young leaves mungbean origin Pelalawan and the eight primer pairs of the g-SSR and EST-SSR were optimized. The optimal Ta for G2436, G3598, G2516, G7472, G0483. G1671, G3302, and G3427 were 50,55ºC, 51,15ºC,51,25ºC, 51,2ºC, 51,6ºC, 49,0ºC, 49,8ºC, and 52,8ºC respectively. Meanwhile, the optimal Ta for E51985, E19823, E24080, E22860, E26637, E16266, E11659, and E10675 were 52,2ºC, 54,4ºC, 52,5ºC,51,25ºC, 53,25ºC, 54ºC, 54,35ºC, and 53,6ºC respectively.